2021
DOI: 10.1016/j.ymthe.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Prodrugs and prodrug-activated systems in gene therapy

Abstract: The inclusion of genes that control cell fate (so-called suicide, or kill-switch, genes) into gene therapy vectors is based on a compelling rationale for the safe and selective elimination of aberrant transfected cells. Prodrug-activated systems were developed in the 1980s and 1990s and rely on the enzymatic conversion of non-active prodrugs to active metabolites that lead to cell death. Although considerable effort and ingenuity has gone into vector design for gene therapy, less attention has been directed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…As a Pak1interacting substrate, dynein light chain phosphorylation controls macropinocytosis [54]. Therefore, phosphorylation-modified GRP75 may significantly modulate this process; (3) we have demonstrated that GRP75-KD or inhibition significantly reduced Rac1 activation [34]. Since Rac1 activation always induces membrane ruffling and macropinocytic cup formation [32], dynamic expression and phosphorylation of GRP75 from S-to M-phase modulate macropinocytosis is logical (Fig.…”
Section: Grp75 Driven Cell-cycle-dependent Macropinocytosis Of Tat/pd...mentioning
confidence: 83%
See 1 more Smart Citation
“…As a Pak1interacting substrate, dynein light chain phosphorylation controls macropinocytosis [54]. Therefore, phosphorylation-modified GRP75 may significantly modulate this process; (3) we have demonstrated that GRP75-KD or inhibition significantly reduced Rac1 activation [34]. Since Rac1 activation always induces membrane ruffling and macropinocytic cup formation [32], dynamic expression and phosphorylation of GRP75 from S-to M-phase modulate macropinocytosis is logical (Fig.…”
Section: Grp75 Driven Cell-cycle-dependent Macropinocytosis Of Tat/pd...mentioning
confidence: 83%
“…The cytotoxic action is localized inside tumor or, if applicable, in neighboring tumor cells that have not been transduced but undergo oncolysis due to the “bystander effect”. The most utilized suicide gene therapy is based on herpes simplex virus-thymidine kinase (HSV-TK) followed by treatment with antiviral drug ganciclovir (GCV), which is transformed to toxic metabolites by the TK action, causing failure of cancer cells in DNA replication and cell apoptosis [ 3 ]. Although suicide gene therapy is in progress, it is far from reaching OC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used suicide genes perform their function via enzymatic drug conversion activity, apoptotic potential, or the ability to direct the immune response against a cell by the addition of a tag ( 126 ). In particular, enzyme prodrugs can enzymatically convert an innocuous prodrug into a toxic compound that can kill the target cell ( 127 ). The toxic molecule generated can act only towards the edited cell or can have a broader action killing also the surrounding cells, called the “bystander effect,” usually used to treat cancer ( 128 ).…”
Section: A Safety Switch For a Safer Cell Therapymentioning
confidence: 99%
“…Gene therapy relies on a cell-specific expression of the chosen protein genes or regulatory RNA either in cancer cells or in effector cells that can be used in therapy. In suicide gene therapy, the genes that encode toxins or prodrugconverting enzymes are used to transduce cancer cells [36]. Ribonucleases are promising agents for use in anticancer therapy, as the production of RNases in the cytoplasm of eukaryotic cells leads to cell death via an apoptosis-mediated pathway [37].…”
Section: Barnase As a Tool For Cancer Suicide Gene Therapymentioning
confidence: 99%